Mathematical models of biofilm growth and food particle degradation in the gastrointestinal tract : a thesis presented in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Nutrition at Massey University, Palmerston North, New Zealand - Van Wey Lovatt, Amy S (Massey University, 2013)
This thesis focuses on two important aspects of digestion: soluble nutrient loss during gastric digestion and the fermentation of digesta by intestinal bacteria. The bioaccessibility of nutrients within a food matrix has become of increasing interest as it is the precursor of bioavailability. pH directly affects enzymatic reactions and has a significant effect on the soluble loss from the food matrix. Analysis of the propagation of acidic water in two model foods showed that the diffusion of the fluid depends on both the pH and the food matrix. Mathematical models were developed to describe the soluble particle loss during gastric digestion at various pH levels and to predict the likely rate of soluble particle loss during digestion Food components that are indigestible in the upper gastrointestinal (GI) tract are likely substrate for the microbiota of the large bowel. The proximity of the microorganisms to one another provides the potential for cross-feeding and competition for nutrients. A modification of a mathematical model was used to characterize the growth kinetics of 18 Bifidobacterium strains. This model was extended to describe nutrient competition and cross-feeding between Bacteroides thetaiotaomicron and two Bifidobacterium species and was able to predict their coculture growth dynamics based on their respective monoculture growth kinetics. While it has been known that the GI tract harbors a diverse bacterial population, biofilms were only recently observed to be associated with the digesta. Biofilm growth is critically dependent on the nutrient availability. Mathematical models that describe nutrient transport within biofilms have made three simplifying assumptions: the effective diffusion coefficient (EDC) is constant, is that of water, and/or is isotropic. Using a Monte Carlo simulation, EDC values were determined, both parallel and perpendicular to the substratum, within 131 single species, three-dimensional biofilms, constructed from confocal laser scanning microscopy images. This study showed that diffusion within bacterial biofilms was anisotropic and depth dependent. A new reaction-diffusion model is proposed to describe the nutrient concentration within a bacterial biofilm that accounts for the depth dependence of the EDC. This thesis enhances our current knowledge in nutrition and microbiology by providing more accurate models that describe food degradation due to acidic hydrolysis and bacterial fermentation.
Keywords: Biofilms; Digestion; Mathematical models; Research Subject Categories::NATURAL SCIENCES::Biology::Organism biology::Animal physiology